Strategies for the prevention of microbial biofilm formation on silicone rubber voice prostheses - Rodrigues, L. R. (2007)
Total laryngectomy, a surgical treatment for extensive cancer of larynx, which alters swallowing and respiration in patients, is followed up with a surgical voice restoration procedure comprising tracheoesophageal puncture techniques with insertion of a ‘‘voice prosthesis’’ to improve successful voice rehabilitation. However, microbial colonization is a major drawback of these devices. Antimicrobials are usually used to prevent the colonization of silicone rubber voice prostheses by microorganisms. However, long-term medication induces the development of resistant strains with all associated risks and the development of alternative prophylactic and therapeutic agents, including probiotics and biosurfactants, have been suggested. The inhibition of microbial growth on surfaces can also be achieved by several other techniques involving the modification of physicochemical properties of the biomaterial surface or the covalently binding of antimicrobial agents to the biomaterial surface. An overview of the different approaches investigated to date and future perspectives to reduce the frequent replacements of voice prostheses in laryngectomized patients through microbial biofilm retardation is presented and discussed.